Everything comes next collected & new poems - Nye, Naomi Shihab 1952- (Greenwillow Books, an Imprint of HarperCollinsPublishers, 2020)
"Everything Comes Next contains Naomi Shihab Nye's most beloved poems, including "Famous," "A Valentine for Ernest Mann," "Kindness," and "Gate A-4," as well as new, unpublished poems. It is an introduction to the poet's work for new readers, as well as a comprehensive edition for classrooms"--
Includes index
Keywords: Jugendlyrik; Kinderlyrik; Englisch; USA; Children's poetry, American; American poetry; JUVENILE NONFICTION / Poetry / General; Children's poetry; Juvenile works; Poetry; Anthologie; Kinderbuch; Jugendbuch